2009
DOI: 10.1016/j.toxicon.2009.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Lopap: A non-inflammatory and cytoprotective molecule in neutrophils and endothelial cells

Abstract: Lopap (Lonomia obliqua prothrombin activator protease) is a member of the lipocalin family isolated from the extract of L obliqua bristles. Lopap displays serine protease-like activities, including coagulation disturbance, cytokine secretion and antiapoptotic activity in human cultured endothelial cells. Here, we have investigated the effects of the recombinant protein (rLopap) on the inflammatory and apoptotic processes of neutrophils and endothelial cells from male Wistar rats. We found that rLopap did not i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 46 publications
0
19
0
2
Order By: Relevance
“…These effects resemble the consumption coagulopathy triggered by the whole venom, indicating the involvement of this prothrombin activator as a key toxin in envenoming [26]. In addition, Lopap is able to modulate endothelial cell responses promoting cell survival, IL-8, nitric oxide (NO) and PGI 2 release, expression of the cell adhesion molecules ICAM-1 and E-selectin, but not VCAM-1 and PCAM-1 [45,77,78]. Lopap also displays cytoprotective activity in neuthrophils and do not modify expressions of L-selectin and β2 integrin.…”
Section: Lopap: Functional Characterization Recombinant Production Amentioning
confidence: 95%
See 1 more Smart Citation
“…These effects resemble the consumption coagulopathy triggered by the whole venom, indicating the involvement of this prothrombin activator as a key toxin in envenoming [26]. In addition, Lopap is able to modulate endothelial cell responses promoting cell survival, IL-8, nitric oxide (NO) and PGI 2 release, expression of the cell adhesion molecules ICAM-1 and E-selectin, but not VCAM-1 and PCAM-1 [45,77,78]. Lopap also displays cytoprotective activity in neuthrophils and do not modify expressions of L-selectin and β2 integrin.…”
Section: Lopap: Functional Characterization Recombinant Production Amentioning
confidence: 95%
“…Lopap also displays cytoprotective activity in neuthrophils and do not modify expressions of L-selectin and β2 integrin. Secretion of the proinflammatory cytokines IL-6 and TNF-α is not changed by Lopap treatment in both cell cultures [78]. Lopap seems to have no effect on modulation of coagulation and fibrinolysis through endothelial cell response, since it does not modify von Willebrand factor (vWF) and tissue plasminogen activator (t-PA) release or tissue factor procoagulant activity on endothelial cell surface [45,77].…”
Section: Lopap: Functional Characterization Recombinant Production Amentioning
confidence: 95%
“…Several studies have shown that, besides its prothrombin activation activity, Lopap demonstrates to exert action on endothelial cell responses [46,48,49] . Endothelial cells respond to external stimuli by altering the secretion or surface expression of biomolecules that regulate vascular tone and permeability, leukocyte traffic, platelet function, blood coagulation and fibrinolysis [50,51] .…”
Section: Lonomia Obliqua Prothrombin Activator Protein (Lopap)mentioning
confidence: 99%
“…On the other hand, NO and PGI 2 produced by endothelial cells have also been implicated as modulators of the leukocyte migration into inflammatory sites, by acting on leukocyte-endothelial interaction steps [53,54] and on expression and activity of adhesion molecules [55,56] . In a recent study [49] it was demonstrated that Lopap does not induce in vivo and in vitro inflammatory properties in neutrophils and endothelial cells (rolling, adherence into vessel wall endothelium, and pro-inflammatory cytokine secretion), thus the biological significance of expression of cytokines and cell adhesion molecules induced by Lopap remains to be clarified. Lopap is also unable to induce in HUVECs the release of pro-thrombotic mediators such as tissue factor and von Willebrand factor, and pro-fibrinolytic mediators such as tissue plasminogen activator (t-PA) [48] .…”
Section: Lonomia Obliqua Prothrombin Activator Protein (Lopap)mentioning
confidence: 99%
See 1 more Smart Citation